Cancelled elective operations and 28-day breaches in the NHS in England: an interrupted time series analysis of the 2002 penalty policy, 2008 recession, and COVID-19 pandemic (1994–2023)Research in context - Laura Quinn; Paul Bird; Timothy P. Hofer; Richard Lilford (The Lancet Regional Health. Europe, 2025)
Summary: Background: In 2002, the English National Health Service (NHS) introduced financial penalties for hospitals failing to provide elective operations within 28 days of last-minute cancellations. This study investigates the impact of this policy, the 2008 global recession, and the COVID-19 pandemic on cancelled operations and breaches of the 28-day standard. Methods: We conducted a retrospective observational study using publicly available NHS England data from 1994 to 2023. Interrupted time series analysis assessed changes in cancelled operations and breaches of the 28-day standard across three key periods: pre- and post-2002 policy implementation, post-2008 recession, and post-COVID-19 pandemic. Subgroup analysis by hospital trust A&E department presence on breaches of the 28-day standard was performed. Findings: Elective admissions nearly doubled over 30 years, rising from just over 1 million per quarter in 1994 (1,054,818) to almost 2 million in 2023 (1,975,508), an 87% increase. Cancellation rates increased leading up to the 2002 policy change but fell rapidly below 1% afterwards and remained stable. The 2008 recession and COVID-19 pandemic did not impact cancellation rates, but did increase breaches of the 28-day standard. Breaches rose before the 2002 policy, dropped rapidly afterwards (−9.6%, 95% CI: −11.2, −9.0), but increased after the recession and notably post-pandemic (13.0%, 95% CI: 4.9%, 21.0%), remaining high and negating earlier gains. Hospitals with A&E departments experienced higher post-pandemic increases in breach rates (12.7%, 95% CI: 10.8, 14.7) compared to those without (0.3%, 95% CI: −3.7, 4.4). Interpretation: The 2002 policy effectively reduced breaches of the 28-day standard for many years but could not be maintained after the COVID-19 pandemic, when breach rates reached high levels, especially hospitals with A&E departments that could not protect elective beds. Effective targets require sufficient resource capacity and demand management, ignoring such constraints can lead to self-defeating, unjust policies. Funding: National Institute for Health and Care Research Applied Research Collaboration West Midlands (NIHR200165).